A Cross-Comparative Survey of Information Seeking and Scanning About Drug-Related Sources and Topics Among U.S. and Israeli College Students. Issue 8 (3rd August 2017) - Cheng, Ying; Ahn, Jisoo; Lewis, Nehama; Martinez, Lourdes S.
Abstract: There is an increasing amount of drug-related information that is easily accessible from media and interpersonal sources. Recent research shows significant positive associations between information acquisition and nonmedical drug use intentions among college students. This study examines information about amphetamines and marijuana that was actively searched ("seeking") as well as information that was encountered during routine media use ("scanning"). Data are drawn from a cross-national comparative survey of college students in the United States ( N  = 734) and in Israel ( N  = 800). U.S. participants reported seeking and scanning information about marijuana across a broader range of sources than Israeli participants. Among U.S. and Israeli participants, the most frequently searched marijuana-related topics included the benefits of marijuana, negative effects of marijuana use, and political reasons why marijuana should be legal. Participants from both countries reported the benefits of amphetamines, and the negative effects of amphetamine use as the most frequently searched topics about amphetamines. Participants in both countries identified the internet and friends as the most popular sources of drug-related information and noted that physicians, friends, and the internet were the most trusted sources. Implications for research on information seeking and health communication are discussed.